Supporting and promoting wellbeing in the higher education sector : practices in action - Dobele, Angela; Farrell, Lisa (Abingdon, Oxon ; New York : Routledge, 2025)
"This book provides innovative, practical tools to help combat declining personal wellbeing in the higher education workplace. Divided into two sections, the book looks at wellbeing from institutional and individual levels. It outlines a framework for how wellbeing in the higher education workplace can be evaluated and clearly sets out initiatives for what can be done to improve faculty wellbeing. The book also explores issues such as the once vocational nature of academia, the extent to which institutions can provide allied health care and examines initiatives that individual faculty members have introduced for themselves. Representing new ideas, perspectives and a variety of approaches to supporting and promoting wellbeing in the higher education workplace, this book will be of interest to academic staff as well as professional development personnel in higher education"--
Part 1. Introduction to Part 1: Faculty wellbeing at institutional and leadership levels / By Angela Dobele and Lisa Farrell -- Academic support / By Drew McHugh and Melanie Trask -- Positive wellbeing within workspaces / By Angela R. Dobele and Lisa Farrell -- Positive wellbeing within workspaces / By Ekant Veer, Mona Soltani and Tracey Robinson -- Part 2. Introduction to Part 2: Wellbeing at the individual level / By Angela Dobele and Lisa Farrell -- Academic identities and wellbeing practices / By Meg Elkins -- Innovative practices for supporting and promoting academic faculty wellbeing in the higher education sector / By Kate Hynes -- Individual wellbeing practices for a post-pandemic university / By Jonathan Boymal, Sam Sterling, Craig Williamson, Ying Zhou and Patrick Lynch -- Conclusion: Lessons learnt / By Angela Dobele and Lisa Farrell.
Keywords: College personnel management; College teachers -- Mental health; Education, Higher -- Psychological aspects; Well-being.; EDUCATION / Higher; EDUCATION / Organizations & Institutions; PSYCHOLOGY / Industrial & Organizational Psychology